Increasing Productivity Long Bean Plant (Vigna Sinensis L) With Organic Vermicompost Fertilizer - Bambang Gunawan; Fauziatun Nisak; Sri Purwanti; Nurlina (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2022)
Long beans are classified as seasonal plants that can begin to be harvested approximately 6-9 weeks after planting and then periodically until approximately 3 months after planting, then the plants experience aging which results in low flower and fruit production. The harvest can be in the form of young pods which contain lots of vitamins A, B and C; medium for the production of mature seeds containing protein, fat and carbohydrates. The productivity achieved by farmers is still much lower when compared to the potential yield of long beans which can reach 20-25 tons/ha of fresh pods. The purpose of the study was to determine the increase in the productivity of long bean plants through the application of organic vermicompost fertilizer. The results of the study provide the following conclusions: There was a significant effect on the treatment of vermicompost on all observed variables, namely plant length, number of leaves, number of fruit (pods) per plant, and fresh weight of fruit (pods) per plant; and giving vermicompost as much as 1.50 kg per plant (treatment K6) gave a better average effect than other treatments at the end of the observation on the variables of plant length, number of leaves, and number of fruit (pods) per plant, although it was not significantly different by giving vermicompost as much as 1.25 kg per plant and 1 kg per plant on the variable total fresh weight of fruit (pods) per plant studied.